1994
DOI: 10.1088/0953-8984/6/50/014
|View full text |Cite
|
Sign up to set email alerts
|

Theory of core-level inelastic X-ray scattering spectra and partial local densities of states in low-Z atom crystals

Abstract: A method for calculating the doubledifferential cross sections of the inelastic x-my scattering (Ixs) associated with low-Z-atom K-level excitation of solids is proposed. We have included both the first-and the second-order contributions of oneelectron perturbxion theory. The secondader contribution is shown to be signiticmt bnly far comparatively amall initial photon energy ( R q c 2 keV). The fist-order term is proved to be determined by p partial local densities of electron states (p wos) whereas the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
2
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
3
2
0
Order By: Relevance
“…(7), jgj has to vary from 36 ± at 190 eV to 63 ± at 192 eV for glancing angle u 5 ± and from 64 ± at 197 eV to 34 ± at 199 eV for glancing angle u 12 ± . Graphite crystal.-The PT of graphite crystal near the K absorption edge have been calculated earlier [6,9]. It has been found that our calculation of the PT is in good agreement with the experimental absorption spectra [3].…”
Section: Sh Machavarianisupporting
confidence: 79%
See 2 more Smart Citations
“…(7), jgj has to vary from 36 ± at 190 eV to 63 ± at 192 eV for glancing angle u 5 ± and from 64 ± at 197 eV to 34 ± at 199 eV for glancing angle u 12 ± . Graphite crystal.-The PT of graphite crystal near the K absorption edge have been calculated earlier [6,9]. It has been found that our calculation of the PT is in good agreement with the experimental absorption spectra [3].…”
Section: Sh Machavarianisupporting
confidence: 79%
“…This anisotropy has a sharp photon energy dependence in the anomalous dispersion region. Our previous calculations of both and XANES in graphite crystal [6] appear to be in reasonable agreement with experimental spectra.Such an anisotropy of the PT leads not only to polarization and orientation dependencies of x-ray spectra but also to differences in fine structures of left and right-hand circularly polarized radiation in both reflectivity [5] and absorption [7] x-ray spectra. Moreover, this anisotropy in combination with the total external reflection gives an opportunity to create an x-ray polaroid device [8,9].…”
supporting
confidence: 85%
See 1 more Smart Citation
“…In principle, this formalism provides the means for model-independent determination of ρ l (ω) from the experimentally measured S ( q ,ω). This was first proposed by Verdrenskii et al…”
Section: Nonresonant X-ray Raman Scatteringmentioning
confidence: 96%
“…For instance, the electronic structure of graphite has been widely studied experimentally and theoretically and the σ * and π * thresholds have been examined by various authors [4,5,12,13]. Theoretically, an intense debate existed around a discrepancy of the position of a peak appearing 3 eV above the Fermi level (ε F ) in the ground state density of states (DOS), whereas experimental XAS observations found that peak shifted to only 1 eV above the C1s onset.…”
Section: Introductionmentioning
confidence: 99%